(untitled) (Fiep Bulletin - online, 2014)
There is no doubt that motor skills represent a very complex field of the psychosomatic dimensions of the human being. Even though a lot of information has been gathered on the subject, the basic problem is that there are very few congruent pieces of information which have been gathered and processed by means of valid and reliable mathematical-statistical procedures. The aim of the research was to determine the quantitative and qualitative differences in terms of motor skills, based on a sample of 240 schoolboys divided into 4 sub-samples of 60 participants each, aged 15-18. For this measuring program the significant motor dimensions were evaluated using 12 measuring instruments. The differences obtained between the four groups of entities were calculated using a program for the canonical discriminant analysis in Mahalanobis space. Following the processing of the data using a program for the canonical discriminant analysis in Mahalanobis space, the obtained results indicated that between the boys, if we take into consideration chronological age, within the entire system (multivariate) of applied motor variables, a statistically significant difference can be found. On the basis of the results obtained in this fashion, we can conclude that the growth trend is such that almost all of the motor skills increase significantly in terms of chronological age. On the basis of the displayed theoretical and practical values of this paper, the authors would like to create the optimal conditions for regular in-class work and extracurricular activities as well as for monitoring, noting and evaluating the sports results of schoolchildren, to increase work intensity in the classroom, to modernize in-class work and to create a greater collaboration between physical education teachers, psychologists, physicians and schoolchildren. On the basis of the obtained and analyzed multivariate and univariate results in this research, generally speaking we can conclude that the results that were obtained were satisfactory and expected.